2021
DOI: 10.1063/5.0043757
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of synthetic fast-ion loss detector and imaging heavy ion beam probe diagnostics in the 3D hybrid kinetic-MHD code MEGA

Abstract: A synthetic fast-ion loss (FIL) detector and an imaging Heavy Ion Beam Probe (i-HIBP) have been implemented in the 3D hybrid kineticmagnetohydrodynamic code MEGA. First synthetic measurements from these two diagnostics have been obtained for neutral beam injectiondriven Alfvén Eigenmode (AE) simulated with MEGA. The synthetic FILs show a strong correlation with the AE amplitude. This correlation is observed in the phase-space, represented in coordinates (P ϕ , E), being toroidal canonical momentum and energy, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Synthetic loss detectors have been produced to compare numerically modeled losses to experimental measurements [14][15][16][17][18]. It has been readily observed that fast ion loss detector (FILD) signals correlate with many loss mechanisms of interest [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic loss detectors have been produced to compare numerically modeled losses to experimental measurements [14][15][16][17][18]. It has been readily observed that fast ion loss detector (FILD) signals correlate with many loss mechanisms of interest [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%